Seasonal study of tillering and phyllochron of winter wheat in field trials - Petróczi, István Mihály; Matuz, János (Acta Biologica Szegediensis, 2002)
In 4-yea r field trials 3 winter wheat (Triticum aestivu m L.) genotypes were studied to identify their shoot and phyllochronal development. Plant samples were picked up 5-8 times in each year from the 1st node to the ripening. The number of tillers achieved the highest rate in the period 6-13 of May in every year. In the late sowings, the decreased source couldn' t be compensated by the increasing number of spikelets and their kernels. The adaptation related mainly to the source-sink ratio. The tillering of cultivar GK Öthalom was more sensitive to the thermal time than the other parent line (GK 44-87). The better productivity of the progeny (cv. GK Miska) were due to the higher shoot and leaf number, but other characteristics were intermediate.